PROGRESSIVE LAW REVEALED: A LEGAL PHILOSOPHICAL OVERVIEW - Erlyn Indarti (Fakultas Hukum, Universitas Diponegoro, 2018)
Progressivism is in essence the principles, beliefs, or practices of progressives, i.e. ones believing in moderate social and political progress in the human condition by means of governmental action. Today’s progressives still fail to offer a coherent account of their core philosophy. They are identified more often by 'what it is not' than by 'what it is'. Progressive law requires the state to embrace a boundless function and use its power to tell people what they must and must not do so as to allow them to get hold of their desired affluence. This concept is embodied in the legal principle Malum Prohibitum. Legal philosophical overview reveals that with this principle progressive law may have the potential to manufacture a system of laws that excessively empowers the state so that liberty is crushed and the light of a free society is replaced with the darkness of tyranny.